Large Artery Atherosclerosis: Extracranial and Intracranial - Banerjee, Chirantan; Turan, Tanya N. (Seminars in Neurology, 2017)
Large vessel atherosclerotic disease (affecting both intracranial and extracranial arteries) is a highly prevalent cause of stroke. In this review, the authors describe the epidemiology, evaluation, diagnosis, and therapeutic aspects of large-vessel atherosclerotic disease. Endarterectomy and stenting have proven to be effective methods for carotid artery revascularization and stroke prevention, although some of the clinical trials demonstrating this benefit predated the advances in modern medical therapy. Randomized clinical trials comparing aggressive management with surgical and endovascular stenting plus aggressive medical management have shown medical management alone to be safer and more effective for preventing stroke in intracranial and vertebrobasilar stenosis.
Keywords: carotid stenosis; ischemic stroke; intracranial atherosclerosis; risk factors